PENGEMBANGAN DAN PEMANFAATAN BAHAN AJAR MODUL DALAM PROSES PEMBELAJARAN - Sungkono Sungkono (MAJALAH ILMIAH PEMBELAJARAN, 2009)
Teachers need the competencies to develop learning material especially module,considering that the development of learning material could contribute to the efficiencyand effectiveness of students learning process. Moreover, learning materials have asignificant role both for teachers and students in individual learning and classical orgroup learning context.Learning using module has some characteristics that are, self instruction, therecognition of individual differences, including the learning objectives/competencies, theoccurrence of existence, structure and knowledge order, the use of multimedia, studentsactive participation, direct reinforcement toward students’ respond, evaluation towardstudents learning.In order to develop module, we need to consider some techniques andcomponents required, such as: the course overview component, introduction, learningactivities, exercises, summary, formative test, and answer key for formative test andfollow up. On the other hand, to develop module we can use some techniques includingstarting from scratch, information repackaging, and compilation.The utilization of module in the learning process can be done in the context ofboth individual learning and group learning system.